SPATIAL RE-CONFIGURATION INITIATIVES FOR INFORMAL-LIKE SETTLEMENT REVITALIZATION: A CASE OF YOGYAKARTA URBAN KAMPONG - Irsyad Adhi Waskita Hutama; Didik Kristiadi (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2019)
Informal-like settlements such as urban kampong is a human habitat which has similar characteristics as an urban slum. They co-exist within urban ecosystem but progressing backward to sub-standard living quality. The recent status of urban kampong is worsened due to lack of basic service and sometimes neglected from spatial plan and program. Spatial reconfiguration is seen as an alternative model to revitalize informal-like urban kampong by creating the condition where the positive loop is available within the kampong. This model can be built by connecting and integrating the inner structure of the kampong's spatial layout to the network of city structure. This research aims to re-configure the spatial arrangement of urban kampong for gradual changes from informal condition to be a more formal, vibrant, and robust neighborhood. This method involves several approaches such as acknowledging the informality of urban kampong, understanding the favorite place and place attachment, reconfiguring new spatial layout, and comparing syntactical properties between existing and new spatial plan. The research result depicts a new spatial design proposal for urban kampong becoming more integrated and connected with the city structure, resulting in the progress of self-regeneration works by itself.